The elicitor preparation retains the ability to induce systemic resistance during storage - Grineva, Irina A.; Kuleshova, Yuliya M.; Lomonosova, Veronica A.; Maslak, Diana V.; Sadovskaya, Ludmila E.; Skakun, Tatyana L.; Feklistova, Irina N.; Maximova, Natalia P. (Experimental Biology and Biotechnology, 2018)
It was established that the elicitor preparation based on bacteria Pseudomonas chlororaphis subsp. aurantiaca 162 and Bacillus subtilis 494 retains the ability to induce systemic resistance for six months at room temperature, and increases reliably the morphological parameters of preparation-processed rapeseed plants under the salinity conditions.